Emerging food safety risk of hepatotoxic indospicine in feral Australian camel meat. (July 2020) - Tan, Eddie T.T.; Ng, Jack C.; Al Jassim, Rafat; D'Arcy, Bruce R.; Netzel, Gabriele; Fletcher, Mary T.
Abstract: Indospicine is a hepatotoxic non-proteinogenic amino acid that has only been found in Indigofera plants including a number of species abundant in central Australia. These legumes are palatable to feral camels and indospicine residues derived from these plants accumulates in camel meat tissue. Indospicine-contaminated camel meat has caused liver disease and mortalities in dogs after a short period of dietary exposure. Since camel meat is also exported for human consumption, this raises concern about the human health risks of consuming indospicine-contaminated camel meat harvested from central Australia. The objective of this study was to assess the indospicine levels in camel meat and its associated potential health risk to the Australian population and the vulnerable sub-population of indigenous Australians from the consumption of such feral camel meat. Two main quantitative probabilistic exposure assessments were conducted through the use of Monte Carlo simulations. The first exposure assessment considered the indospicine concentrations in real-field camel meat samples. The second assessment was based on a simulated probabilistic distribution of indospicine residues in camel meat, involving eight (8) predictive factors that were derived from our published research data and other secondary sources. The first assessment predicted that the estimated risk of developing indospicine₋induced hepatotoxicosis from contaminated camel meat consumption was 800 per 10 000 of the average Australian population (8.0%), and higher for the indigenous Australians (10.0%). The second exposure assessment demonstrated there was a higher risk (>31%) for the whole Australian population and for the indigenous Australian population. In conclusion, this risk assessment study shows that, while there is a low risk amongst Australians of hepatotoxicosis being associated with the consumption of indospicine-contaminated camel meat, such consumption is still a cause for concern, since the assessment based on the simulated probabilistic distribution of indospicine concentrations in camel meat demonstrated a substantially higher risk. It is therefore advisable that an indospicine residue monitoring program should be implemented to ensure food safety of Australian camel meat. Additionally, the risk of dietary indospicine exposure from other livestock grazing Indigofera in all global regions should also be considered. Graphical abstract: Image 1 Highlights: Heptatotoxic indospicine forms residues in meat tissue of camels grazing Indigofera . Dogs have died from eating contaminated meat and human health risk is of concern. Quantitative probabilistic exposure assessments characterised potential health risk. Assessments based on real-field camel meat samples suggest low health risk. Residue monitoring program warranted to ensure food safety of Australian camel meat.